Wing coupling mechanism in the butterfly Pieris rapae (Lepidoptera, Pieridae) and its role in taking off. (May 2021) - Ma, Yun; Zhao, Hongyan; Ma, Tianbao; Ning, Jianguo; Gorb, Stanislav
Graphical abstract: Highlights: Amplexiform coupling includes a forewing basal area and a hindwing humeral area. Coupling-clipping induces unsynchronization of fore- and hindwing flapping motion. Coupling-clipped butterflies could take off successfully. More tilted strokeplane and enhanced abdomen undulation ensure successful takeoff. Abstract: The small white cabbage butterfly ( Pieris rapae ) flaps its fore- and hindwings in synchrony as the wings are coupled using a wing "coupling mechanism". The coupling mechanism of butterflies includes an enlarged humeral area located at the anterior of the hindwing base and a corresponding basal posterior part of the forewing, of which the former component dorsally contacts the ventral side of the latter one. The coupling mechanism allows for the fore- and hindwings sliding in contact along the span and chord. It is of interest that butterflies still take off successfully and fly, when their wing couplings are clipped, but they are unable to properly synchronize the fore- and hindwing motions. Compared with the regular takeoff trajectory of intact butterflies that always first fly backwards and then forwards, the coupling-clipped butterflies took off in a random trajectory. Due to the clipping of the coupling mechanism, the initiation of the hindwing flapping and the abdomen rotation from upward to downward during takeoff was postponed. The coupling-clipped butterflies changed their stroke plane in upstroke to a more vertical position and strengthened the abdominal undulation. We believe our work, which for the first time investigates the influence of coupling mechanism removal on insect flight, extends our understanding on the working principle of wing coupling in insects and its significance on the flapping flight.